The Influence of Service Quality, Trust, and Consumer Satisfaction on Consumer Loyalty (Case Study Of Cv.Lima Satu Tiga Transportation Services) - Ade Prayoga; Lilik Nurcholidah (Research Trend in Technology and Management, 2025)
The purose of the company in marketing is to create cuctomer loyality.The existence of customer loyality can provide benefits to a company because it can maintain and compete with is competitors. The sample this is study was 86 customers of the CV. Lima Satu Tiga transportation service. The results of the study showed that simultaneously Service Quality, Trust and Consumer Satisfaction had a significant effect on Consumer Loyalty at CV. Lima Satu Tiga. Partially each variable Service Quality, Trust and Consumer Satisfaction had a positive and significant effect on Consumer Loyality at CV. Lima Satu Tiga.